2020
DOI: 10.1371/journal.pone.0232581
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes, breast cancer specific and overall mortality: Associations by metformin use and modification by race, body mass, and estrogen receptor status

Abstract: Introduction While type 2 diabetes (T2D) has been associated with increased all-cause mortality among women diagnosed with breast cancer (BC), the association between T2D and breast cancer-specific (BCS) mortality is unresolved. The goal of this study was to examine the association between T2D and BCS mortality and examine the influence of metformin treatment on mortality rates. Methods A retrospective cohort study was conducted between 2002 and 2008 at Emory University Hospitals among non-Hispanic black and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…18 Recently, several studies reported that type 2 diabetes and impaired glucose metabolism were associated with the prognosis of breast cancer. [19][20][21][22] In our study, an IGT was associated with SLN metastasis. Our findings suggest that having IGT may lead to LN progression despite early breast cancer.…”
Section: Discussionsupporting
confidence: 55%
“…18 Recently, several studies reported that type 2 diabetes and impaired glucose metabolism were associated with the prognosis of breast cancer. [19][20][21][22] In our study, an IGT was associated with SLN metastasis. Our findings suggest that having IGT may lead to LN progression despite early breast cancer.…”
Section: Discussionsupporting
confidence: 55%
“…Of note, metformin is consistently shown to be associated with lower mortality in a range of conditions (e.g., breast cancer [ 45 ], not just COVID-19). These associations are not presumed to be causal, and these findings should not be immediately interpreted as suggesting that metformin has a protective effect in COVID-19 illness without further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Obesity and metabolic disease poses a deepening challenge in the United States, where the burden of Type 2 diabetes (T2D) or pre-diabetes affects over 100 million adults ( 1 – 4 ). Critically, these diseases are implicated in a variety of cancers, both with an obesogenic environment, such as endometrium, colon, and kidney, as well as less common malignancies such as leukemia, multiple myeloma, and non-Hodgkin’s lymphoma ( 5 ).…”
Section: Introductionmentioning
confidence: 99%